PENGARUH CAPITAL ADEQUACY RATIO, NON PERFORMING LOAN, LOAN TO DEPOSIT RATIO DAN EFISIENSI OPERASIONAL TERHADAP PROFITABILITAS PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sofia Prima Dewi (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2014)
This study aims to obtain empirical evidence whether the capital adequacy ratio, nonperforming loans, loan to deposit ratio and operational efficiency has an influence on bank profitability. The samples used were 27 banking companies listed on the stock exchange Indonesia during the years 2011-2013. Data analysis was performed with the help of a software program Statistical Product and Service Solutions (SPSS) for Windows version 16.00. The results showed that the operational efficiency has an influence on bank profitability, while capital adequacy ratio, non-performing loans dan loan to deposit ratio has no effect on bank profitability.